Metal-free aerobic oxidative coupling of amines in dimethyl sulfoxide via a radical pathway. Issue 13 (26th January 2016) - Lin, Mu; Wang, Zikuan; Fang, Huayi; Liu, Lianghui; Yin, Haolin; Yan, Chun-Hua; Fu, Xuefeng
Abstract : Metal-free oxidative coupling of amines is achieved simply by heating their dimethyl sulfoxide (DMSO) solution under oxygen, accompanied by the formation of an equimolar amount of dimethyl sulfone (DMSO2 ). Abstract : Metal-free oxidative coupling of amines is achieved simply by heating their dimethyl sulfoxide (DMSO) solution under oxygen as oxidant without any other catalysts or additives, accompanied by the formation of an equimolar amount of dimethyl sulfone (DMSO2 ). EPR experiments indicate that the reaction proceeds via a radical pathway. DMSO may play a triple role as solvent, radical initiator and co-reductant.